Predictors of student misbehavior in Jordanian high schools - Mahasneh, Ameen Mohammed Mousa (2012)
Despite the number of studies examining student misbehaviour in school,there is still much to be learned in this field, specifically on student misbehaviour in Jordanian high schools. The main objective of this study is to identify predictors of student misbehaviour in Jordanian high schools in the Governorate of Jarash. It aims to identify the types and levels of misbehaviour exhibited by students, to investigate the relationship between student misbehaviour and the students’ attachment and commitment to school, their involvement in school activities, their beliefs in the importance of common school rules, parental attachment and involvement in their education, students’ perceptions of their peer group and their teachers’ behaviour towards them. The research design for this study was quantitative in nature and employed the descriptive correlational research design. The data were analyzed using the independent sample t-test, One Way Analysis of Variance (ANOVA), Pearson Product Moment Correlation and stepwise multiple regression. The sample of this study consisted of four hundred and forty-three (443) high school students in the Jordanian Governorate of Jarash, 216 were males and 227 females. A questionnaire was adopted based on Hirschi’s Social Bond Theory, Durkheim Theory of morality and Islamic perspective of moral education which formed the theoretical basis of the study. The findings show that the levels of misbehaviour amongst Jordanian high school students were generally low and that the most common types of misbehaviour were disobedience, followed by classroom disruption, and vandalism. The results of this study also revealed that the level of student misbehaviour significantly differed in relation to gender, grade level, types of school, and parents’ educational background. The stepwise multiple regression analysis showed that nine out of seventeen predictor variables are directly related to student misbehaviour. The significant predictors adopted from Hirschi’s Social Bond Theory are beliefs in the importance of common school rules, commitment to school, attachment to school, and parental attachment towards children’s education.Demographic variables such as gender, grade level, types of school,academic achievement, and father’s level of education (if he had never attended school) also served as significant predictors. However, independent variables such as father’s level of education (if he had attended secondary school and lower), mother’s level of education, students’ involvement in school activities, parental involvement, students’ perception of their peer group and that of the teachers’ behaviour towards them were not found to be significant in predicting student misbehaviour in Jordanian high schools. The findings suggest that all parties, including the Ministry of Education,teachers as well as parents need to achieve a higher level of cooperation in order to improve students discipline in Jordanian high schools.